Associations of Serum Cathepsin K and Polymorphisms in CTSK Gene With Bone Mineral Density and Bone Metabolism Markers in Postmenopausal Chinese Women - Gao, Li-hong; Li, Shan-shan; Yue, Hua; Zhang, Zhen-lin (Frontiers in Endocrinology, 2020)
Cathepsin K plays an important role in bone resorption. The reports of the association of serum cathepsin K with bone mineral density (BMD) and bone turnover markers are conflicting and the role of serum cathepsin K as a bone turnover marker is unclear. The aims of the study were as follows: 1) to investigate the association of serum cathepsin K with BMD and markers of bone turnover and 2) to evaluate the correlations of single-nucleotide polymorphisms (SNPs) within the CTSK gene with serum cathepsin K, BMD, and markers of bone metabolism in postmenopausal Chinese women. A cross-sectional study was conducted with 1752 postmenopausal Chinese women. Four tagging SNPs (rs12085336, rs12746973, rs4379678 and rs10847) of the CTSK gene were genotyped. Serum cathepsin K of 768 and markers of bone metabolism of 1752 including serum intact PTH, 25-hydroxyvitamin D [25(OH)D], procollagen type 1 N-terminal propeptide (P1NP), and β-CrossLaps of type I collagen containing cross- linked C-telopeptide (β-CTX) were measured. The BMD of the lumbar spine and proximal femur were measured by dual-energy X-ray absorptiometry (DXA). No significant relationship was detected between serum cathepsin K and age, BMI, BMD or bone metabolic markers (all P >0.05) after adjustment for age and BMI. We failed to identify any significant association between the genotypes or haplotypes of CTSK and BMD, bone turnover markers, or serum cathepsin K. Neither serum cathepsin K nor CTSK gene polymorphisms was correlated with BMD or bone turnover markers. Genetic polymorphisms of CTSK may not be a major contributor to variations in the serum cathepsin K or BMD in postmenopausal Chinese women. The results implied that serum cathepsin K may not be viewed as a substitute for bone turnover markers.